Modernization of the child neglect and delinquency prevention system: basic models - Sergun, Petr; Starodubov, Arsenii; Ilgova, Ekaterina; Kuznetsova, Irina; Gorbachev, Mikhail (International Journal of Psychosocial Rehabilitation, 2020)
In any society juveniles are a vulnerable group which needs care and safeguard from dangers, threats, and temptations of the permanently complicating world. Any government realising the young generation importance and significance for its future defends and guards children and youth through a corresponding policy specially worked out. In the Russian Federation a child neglect and delinquency prevention system foundation was laid in 1999 by passing a cognominal Federal Law that is almost twenty years ago. The child neglect and delinquency prevention system existing in Russian Federation nowadays is outof-date and does not meet modern challenges and threats. Therefore, the purpose is to consider modernization of this system. During analysis a special attention is given to commissions on juvenile affairs and protection of their rights in the future institutional models of the child neglect and delinquency prevention system. In this article models of child neglect and delinquency prevention system modernization are offered, criteria are worked out. The authors assess child neglect and delinquency prevention system functional possibilities in case of its changes within each of the suggested modernization models. The system of prevention of neglect and juvenile delinquency can be upgraded within the framework of four basic models. The choice of a particular model depends on many factors, the most important of which may be the assessment of the effectiveness of the entire system of prevention carried out by public authorities and independent public institutions.